A loss of host-derived MMP-7 promotes myeloma growth and osteolytic bone disease in vivo - Lwin, S; Fowler, J; Drake, M; Edwards, J; Lynch, C; Edwards, C (Springer Verlag, 2017)
Matrix metalloproteinases (MMPs) play a critical role in cancer pathogenesis, including tumor growth and osteolysis within the bone marrow microenvironment. However, the anti-tumor effects of MMPs are poorly understood, yet have significant implications for the therapeutic potential of targeting MMPs. Host derived MMP-7 has previously been shown to support the growth of bone metastatic breast and prostate cancer. In contrast and underscoring the complexity of MMP biology, here we identified a tumor-suppressive role for host MMP-7 in the progression of multiple myeloma in vivo. An increase in tumor burden and osteolytic bone disease was observed in myeloma-bearing MMP-7 deficient mice, as compared to wild-type controls. We observed that systemic MMP-7 activity was reduced in tumor-bearing mice and, in patients with multiple myeloma this reduced activity was concomitant with increased levels of the endogenous MMP inhibitor, tissue inhibitor of metalloproteinases-1 (TIMP-1). Our studies have identified an unexpected tumour-suppressive role for host-derived MMP-7 in myeloma bone disease in vivo, and highlight the importance of elucidating the effect of individual MMPs in a disease-specific context.